EMANSIPASI WANITA DAN PERAN IBU (KAJIAN TEMATIK DAN PSIKOLOGIS PENDIDIKAN ANAK USIA DINI) - Ivan Riyadi (Al-Afkar : Jurnal Keislaman & Peradaban, 2015)
Based on the thematic and psychological studies that the role of the mother is very significant for young children, mothers act as educators and models for children. Then this article aims to explore which refers to the books of literature, using the form of theories, concepts, where the presentation is descriptive by using research methods literature. Challenges to be faced by the woman currently in the pro - emancipation, which must be running multiple roles without having to leave his nature as a woman . On one hand , Women are required to always be « productive « in the career and life of its people . However , on the other hand for a woman who has not had a partner they should serve the elderly . And if it already has a spouse, a woman devoted to her husband prosecuted . As well as being a mother and role model for his children . That is what will be the biggest challenge for the woman